Radio Absorption in the Nightside Ionosphere of Mars During Solar Energetic Particle Events - Y. Harada; Y. Nakamura; B. Sánchez‐Cano; M. Lester; N. Terada; F. Leblanc (Space Weather)
Abstract Characterization, understanding, and prediction of the Martian radio environment are of increasing importance to the forthcoming human exploration of Mars. Here we investigate 3–5 MHz radio absorption in the nightside ionosphere of Mars caused by enhanced ionization at <100 km altitudes during solar energetic particle (SEP) events. We conduct a quantitative analysis of radio absorption and SEP flux data that have been accumulated by two spacecraft currently orbiting Mars, thereby demonstrating that radio absorption is clearly correlated with SEP fluxes. A comparison of the observations with radio absorption properties predicted by a numerical model indicates that the relative temporal changes, radio frequency dependence, and SEP energy dependence of the observed radio absorption are in agreement with the model prediction. Meanwhile, the model systematically overestimates the radio absorption in the ionosphere by a factor of 3.7. We explore several sources of uncertainty, including the electron‐neutral collision frequency, absolute sensitivity of the SEP instrument, and limited transport of SEPs to the atmosphere, but the ultimate cause of the systematic discrepancy between the measured and modeled radio absorption is yet to be identified. Further efforts should be put into the development of a comprehensive and observationally validated model of radio absorption in the Martian ionosphere to assist the future crew and spacecraft activities on the surface of Mars.